Why anarchists like zen? A libertarian reading of Shinran (1173-1263). Essays in anarchism and religion - Galván-Álvarez, Enrique (Stockholm University Press, 2024)
Most attempts to formulate a Buddhist anarchism in the West take Zen Buddhism as their reference point, often disregarding other Buddhist traditions and their anarchic/libertarian potential. In re- sponse to these early Western formulations I propose an alternative pathway for Buddhist anarchism based on a radically different Buddhist tradition, that of Shinran Shonin (1173–1263). Shinran’s thought can arguably contribute to contemporary Buddhist anar- chism some of the elements that it seems to be lacking: a self-critique that is not devoid of social criticism, a deconstruction of Buddhist power and an historical awareness. For this purpose, I will first outline some of the anti-authoritarian traits in Shinran’s writings, which have so far not been read from an explicitly anarchist angle. Then I will look closely at Shinran’s critical view of humanity and human relations through his concept of mappo, drawing out the egalitarian and subversive implications of Buddhist eschatology. In so doing I show how Shinran’s radical re-reading of the Buddhist canon, and the self-understanding it yields, bring into question some important narratives that legitimize and construct the estab- lished, politico-religious order.
Keywords: religious anarchism; religion and politics; anarchism; Theology